Strategic Thinking and Suggestions on Promoting Regional Energy Revolution Based on Local Conditions - Xie Kechang (《中国工程科学》杂志社, 2021)
The coordinated development of energy, economic society, and ecological environment has always been one of the major issues facing China. Although achievements have been made in some regions in China regarding the coordinated development, varied contradictions and problems still exist. Therefore, China should consider these significant differences in regional development while promoting energy revolution. This study elaborates the significance of regional energy revolution and analyzes the current status of economic society, energy, and ecological environment in the Beijing–Tianjin–Hebei region, Yangtze River Delta, Pearl River Delta, old industrial bases, the central region, energy-rich areas, and the Southwest in China. To promote the regional energy revolution, China should strengthen the top-level design for energy revolution and clarify the strategic objectives and key tasks for medium- and long-term development. A mode of well-planned and coordinated development should be established by clarifying the functions of regional energy revolution. The pilots of regional energy revolution should be promoted, thus to explore an efficient mechanism for the energy revolution. Moreover, the responsibilities of the regional governments should be clarified and an assessment and supervision mechanism should be established, so as to ensure that the regional energy revolution achieves expected effects.